Direct Selling : A Global and Social Business Model. - Cochran, Sara L. (Studien Zum Physik- und Chemielernen Series, 2021)
Direct Selling: A Global and Social Business Model is a collective project from eight academics and practitioners who have dedicated much of their careers to understanding direct selling as both a go-to-market strategy and a channel of distribution and to capturing the people who are the foundation of direct selling. The pages of this book bring together a wealth of research and knowledge that can inform a broad spectrum of constituents about the economic and social benefits of direct selling, while also providing detail and clarity on key issues related to direct selling as a sustainable business model.